DIGITAL TRANSFORMATION FOR SUSTAINABLE DEVELOPMENT: BLURU KIDUL VILLAGE - Priyona, Atha Yumna; Agustina, Isna Fitria (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to describe the implementation of digital transformation in Bluru Kidul Village, which covers three main focuses, namely public services, MSME empowerment, and increasing community digital literacy. Method: The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews and observation. The theories used are Diffusion of Innovation by Everett Rogers and the concept of Sustainable Development from the Brundtland Report. Results: The results of the study show that digitization has accelerated public administration services, helped promote and facilitate transactions for SME actors, and increased community participation in digital technology, although there are still challenges in terms of equitable access and human resource capacity. Novelty: This study confirms that digital transformation can be a driving force for sustainable development if it is supported by regulations, collaboration, and equitable digital literacy.